2021
DOI: 10.1177/1455072520985974
|View full text |Cite
|
Sign up to set email alerts
|

Drinking motives and their associations with alcohol use among adolescents in Sweden

Abstract: Aims: Previous studies have shown a close association between drinking motives and drinking behaviour among adolescents. However, there is a lack of evidence from the Nordic countries since few studies covering this topic have been carried out in this context. The present study among Swedish adolescents aims to examine (1) the prevalence of different drinking motives, (2) how drinking motives are associated with drinking frequency and heavy drinking frequency, and (3) whether the associations are moderated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 34 publications
7
15
0
1
Order By: Relevance
“…Our results echo those of two recent qualitative studies from Norway [27] and Sweden [28] that also concluded that the cultural position of alcohol has changed among adolescents. The qualitative findings suggest that alcohol has lost its importance in socializing situations between peers and that today's adolescents do not perceive any peer pressure to drink [28] which is also supported by quantitative findings of drinking motives among Swedish youth [29].…”
Section: Discussionsupporting
confidence: 52%
“…Our results echo those of two recent qualitative studies from Norway [27] and Sweden [28] that also concluded that the cultural position of alcohol has changed among adolescents. The qualitative findings suggest that alcohol has lost its importance in socializing situations between peers and that today's adolescents do not perceive any peer pressure to drink [28] which is also supported by quantitative findings of drinking motives among Swedish youth [29].…”
Section: Discussionsupporting
confidence: 52%
“…Rats were randomly assigned to two experimental groups (n = 7 per group): alcohol naïve (CTRL) rats and bingelike alcohol-exposed (BAW) rats. BAW rats were exposed to alcohol in an intermittent binge-like alcohol paradigm during adolescence (PND [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The 25% alcohol solution was daily prepared and administered per os (38), at the dosage of 3.5 g/kg (39), 3 days a week, every other day, for a total of 9 exposure, as previously described (30).…”
Section: Anxiety-like Phenotype and Stress Reactivity Evaluation In A...mentioning
confidence: 99%
“…Adolescence also involves the discovery of new activities, such as alcohol use [10]. As drinking is mainly a social activity [11,12], social processes like trust should theoretically be of importance. Given that the formation of trust and the initiation of alcohol drinking both occur during adolescence, it is important to understand how these two relate to each other.…”
Section: Introductionmentioning
confidence: 99%